Psychological risk factors and cardiovascular disease - Carola, Valeria; Vincenzo, Cristina; Di Vincenzo, Giulia; Morale, Chiara; Cecchi, Valentina; Nicolais, Giampaolo (Frontiers in Psychology, 2024)
Objectives Cardiovascular diseases (CVDs) are a leading cause of death worldwide, emerging from a combination of several factors. The aim of this review is to define the psychological factors that are significant in the development and progression of these disorders. Methods Studies published through 2023 concerning adults with psychological vulnerability factors and/or cardiovascular disease were selected through searches of PubMed, PsychINFO, Science Direct, and Google Scholar. Results Psychological stress may influence CVD, in combination with other risk factors, or it can act independently, as in cases of workplace stress, post-traumatic stress disorder, Takotsubo syndrome and bereavement. Coping strategies, anxiety and depression have also been identified as relevant psychological factors in cardiac patients. Adverse childhood experiences are linked to a reduced quality of life and have been identified as significant risk factors for the development of acquired CVDs. Conclusion This review demonstrates that several psychological factors affect cardiovascular function. An in-depth study of the psychological correlates of CVDs would allow healthcare professionals to design more effective prevention and intervention programs.